The fictionalization of Joaquin Guzman Loera leak in the Mexican press. A study of the the characterization in Reforma, El Universal, la Jornada and Excélsior newspapers (2015) (2017)
Reporting on drug trafficking could be considered complex from any point of view. The difficulties of those aspects of journalism are compounded even more so in Mexico which is considered one of the most dangerous countries in the world for reporters. This paper will show the results of a content-analysis in the four main Mexican newspapers about the journalistic production related to the escape of Joaquin Guzmán Loera from Altiplano Penitentiary, a case that generated enormous international interest. The analysis of the data reveals that Mexican journalists' reporting tended to construct a narrative that varied between sensationalism and culture of fear.